Vestibular-guided visual search - Smith, Laura (Exp Brain Res, 2020)
The amnesic symptoms that accompany vestibular dysfunction point to a functional relationship between the vestibular and visual memory systems. However, little is known about the underpinning cognitive processes. As a starting point, we sought evidence for a type of cross-modal interaction commonly observed between other sensory modalities in which the identification of a target (in this case, visual) is facilitated if earlier coupled to a unique, temporally coincident stimulus from another sensory domain (in this case, vestibular). Participants first performed a visual detection task in which stimuli appeared at random locations within a computerised grid. Unknown to participants, the onset of one particular stimulus was accompanied by a brief, sub-sensory pulse of galvanic vestibular stimulation (GVS). Across two visual search experiments, both old and new targets were identified faster when presented in the grid location at which the GVS-paired visual stimulus had appeared in the earlier detection task. This location advantage appeared to be based on relative rather than absolute spatial co-ordinates since the effect held when the search grid was rotated 90°. Together these findings indicate that when individuals return to a familiar visual scene (here, a 2D grid), visual judgements are facilitated when targets appear at a location previously associated with a unique, task-irrelevant vestibular cue. This novel case of multisensory interplay has broader implications for understanding how vestibular signals inform cognitive processes and helps constrain the growing therapeutic application of GVS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00221-020-05741-x) contains supplementary material, which is available to authorized users.